Effect of inorganic sulfide on the growth and metabolism of Methanosarcina barkeri strain DM. - Mountfort, D O (1979)
Minimal growth of Methanosarcina barkeri strain DM occurred when sulfide was omitted fromthe growth medium, and addition of either sodium sulfate or coenzyme M to sulfide-depleted media failed to restore growth. Optimal growth occurred in the presence of 1.25 mM added sulfide, giving a molar growth yield (YCH4) of 4.4 mg (dry weight) of cells per mmol of CH4 produced. Increasing sulfide to 12.5 mM led to decrease in YCH4 (1.9 mg [dry weight]/mmol of CH4), in the specific growth rate and in be intracellular levels of adenosine triphosphate. However, the specific rate of methane production increased. The data suggested that at elevated sulfide levels (12.5 mM) the decrease in YCH4 might be a result of an increase in the relative energy needed for maintnenace and of uncoupling of growth from energy production.